2012
DOI: 10.1016/j.schres.2012.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents at ultra-high risk for psychosis with and without 22q11 deletion syndrome: A comparison of prodromal psychotic symptoms and general functioning

Abstract: Even if the two UHR groups are comparable in terms of positive symptoms, the UHR+22q11DS have a specific clinical pattern characterized by higher negative symptoms, lower general functioning and an older age of onset of the UHR state. This finding may be of clinical value for the development of specific therapeutic intervention for UHR+22q11DS, and of theoretical value since the two groups may share only some underlying etiopathogenetic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 62 publications
5
33
0
1
Order By: Relevance
“…[42][43][44] The collective prevalence rates of those with positive subthreshold symptoms (32.8%) and those with negative/ disorganized subthreshold symptoms (21.7%) sum up to 54.5%, which is similar to the 54% who met criteria for "psychosis-proneness" in the research conducted by Tang et al 5 Similarly, the rates of negative/disorganized subthreshold symptoms found in our cohort parallel those reported in several previous studies with 22q11.2DS individuals, suggesting that negative symptoms are common in this population. 11,22 Negative symptoms are considered important predictors of the likelihood to convert to psychosis in high-risk populations without 22q11.2DS. 11,45 For example, moderate and severe subthreshold negative symptoms were highly abundant in individuals at high risk for psychosis in the North American Prodrome Longitudinal Study (NAPLS), and the severity and persistence of these symptoms were positively associated with transition rates into a psychotic state at 6-and 12-months post-baseline visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44] The collective prevalence rates of those with positive subthreshold symptoms (32.8%) and those with negative/ disorganized subthreshold symptoms (21.7%) sum up to 54.5%, which is similar to the 54% who met criteria for "psychosis-proneness" in the research conducted by Tang et al 5 Similarly, the rates of negative/disorganized subthreshold symptoms found in our cohort parallel those reported in several previous studies with 22q11.2DS individuals, suggesting that negative symptoms are common in this population. 11,22 Negative symptoms are considered important predictors of the likelihood to convert to psychosis in high-risk populations without 22q11.2DS. 11,45 For example, moderate and severe subthreshold negative symptoms were highly abundant in individuals at high risk for psychosis in the North American Prodrome Longitudinal Study (NAPLS), and the severity and persistence of these symptoms were positively associated with transition rates into a psychotic state at 6-and 12-months post-baseline visits.…”
Section: Discussionmentioning
confidence: 99%
“…Among these are longitudinal decline in verbal IQ (VIQ), 17,18 lower baseline IQ, 3,8,19 the presence of comorbid anxiety disorders, 7,8,20 and lower global functioning. 21,22 However, the comorbidity of these conditions with subthreshold psychotic symptoms has not been sufficiently explored. Moreover, assessment of this phenomenon in 22q11.2DS individuals of various ages is vital for elucidating the rate and nature of subthreshold psychotic symptoms across development in this population.…”
mentioning
confidence: 99%
“…Thus, negative symptoms appear to be one of the clinical characteristic of 22q11DS since they are present in roughly a third of patients in the absence of positive symptoms (Schneider et al, 2014b). Additionally, negative symptoms are more severe in patients with 22q11DS at risk for developing psychosis compared to at-risk subjects without the microdeletion (Armando et al, 2012;Tang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research supports a relationship between early onset psychosis and poor prognosis (Lay et al, 2000; Remschmidt, 2002) suggesting that treatment of deficits early on may be helpful (Mcglashan and Johannessen, 1996). Thus, examining adolescents with 22q11DS could offer a unique opportunity to investigate specific and early interventions related to potential psychotic onset (Armando et al, 2012). …”
Section: Introductionmentioning
confidence: 99%